The Impact of Psychological Policy on the Sports Performance of NPC Makassar City Disabled Athletes - Andi Muhammad Fadlih; Muh Qasash Hasyim; Muh Anugrah Setyawan; Dilli Dwi Kuswoyo (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The challenges faced by athletes with disabilities in sports are closely linked to their psychological well-being. Optimal performance can be achieved when an athlete is fully prepared to compete with all their abilities, encompassing both physical and psychological readiness. A study was conducted to examine the impact of emotional regulation on the performance of disabled athletes at the NPC Makassar City. The objective of this research is to explore the influence of Psychological Policy on the Sports Performance of Makassar City NPC Disabled Athletes. Materials and methods. The research conducted is quantitative in nature, using an analytical observational design with a cross-sectional approach. The study took place at NPC Makassar City and involved the NPC athletes of Makassar City, with a total population of 160 athletes. Random sampling was used as the sampling technique, and data collection methods included questionnaires, observations, and documentation. Results. The process of hypothesis testing involves using the Product Moment Correlation technique. The research findings indicate a strong correlation between emotional regulation and the performance of NPC Makassar Athletes (t-count > t-table (8.685 > 1.571). Conclusion. Based on the results of data analysis, it can be concluded that there is a strong correlation between emotional regulation and the sports performance of Makassar City NPC athletes. This is supported by the t-test results, which indicate that the t-value (8.683) is greater than the critical t-value (1.571), leading to the rejection of the null hypothesis (Ho) and demonstrating statistical significance